An Overview on Biological Concept of Microbial Fuel Cells - Kumar, Ravinder; Singh, Lakhveer; Zularisam, A. W. (Penerbit Universiti Malaysia Pahang, 2014)
The microorganisms such as bacteria act as biological catalysts in microbial fuel cells (MFCs). These microorganisms oxidize the organic matter at the anode and transfer the electrons exogenously to the electrode surface (anode surface) without any need of artificial mediators. Such microorganisms have been referred as exoelectrogens. They form conductive biofilms on the electrode surface, metabolize the substrates into electrons, protons and carbon dioxide. The exoelectrogens produce some redox proteins such as c-type cytochromes and pili for direct electron transfer, and some electron shuttles e.g., pyocyanin for mediated electron transfer.